The Hemostasis System During MARS Therapy and Plasma Sorption in Patients with Liver Cell Failure - L. F. Yeremeyeva; A. F. Yampolsky; I. B. Zabolotskikh; V. V. Menshchikov (Общая реаниматология)
Objective: to comparatively estimate major hemostatic parameters during plasma sorption (PS) and molecular adsorption recirculating system (MARS) therapy in patients with liver cell failure. Subjects and methods: Forty-one patients with liver cell failure were examined. The patients’ condition was rated using the APACHE III, SOFA, MODS, and Child-Pugh scales. As a complex of intensive therapy, all the patients were treated with extracorporeal techniques: MARS therapy in Group 1 (n=17) and plasma sorption in Group 2 (n=24). The patients’ age was 18 to 65 years. Results. MARS therapy, unlike PS, normalizes the parameters of coagulation hemostasis and stabilizes platelet counts within 5 days in the postperfusion period. MARS therapy is the procedure of choice for the treatment of patients with liver cell failure. Mortality was 35.3 and 54.2% in Groups 1 and 2, respectively. Key words: molecular adsorption recirculating system, plasma sorption, acute liver cell failure.